2013
DOI: 10.2460/ajvr.74.6.835
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of terbinafine after oral administration of a single dose to Hispaniolan Amazon parrots (Amazona ventralis)

Abstract: Analysis of the results indicated that oral administration of terbinafine at a dose of 60 mg/kg to Amazon parrots did not result in adverse effects and may be potentially of use in the treatment of aspergillosis. Additional studies are needed to determine treatment efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…71,72 Voriconazole induces its own metabolism via cytochrome P450 and doses should be increased over time. 95 Hispaniolan Amazon parrot 79 60 mg/kg q24 h Regurgitation in red-tailed hawk 80 Often combined with azoles 71 Dose should be decreased in cases on impaired renal function 57 Red-tailed hawk 80 22 mg/kg q24 h African penguin 81 15 mg/kg q24 h…”
Section: (Molds) St (Yeasts)mentioning
confidence: 99%
See 1 more Smart Citation
“…71,72 Voriconazole induces its own metabolism via cytochrome P450 and doses should be increased over time. 95 Hispaniolan Amazon parrot 79 60 mg/kg q24 h Regurgitation in red-tailed hawk 80 Often combined with azoles 71 Dose should be decreased in cases on impaired renal function 57 Red-tailed hawk 80 22 mg/kg q24 h African penguin 81 15 mg/kg q24 h…”
Section: (Molds) St (Yeasts)mentioning
confidence: 99%
“…Data from Refs. 57,69,71,72,75,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] Succimer (meso 2,3-dimercaptosuccinic acid or DMA) is an oral chelator, derived from British Anti-Lewisite capable of chelating lead from soft tissues, but not from bone. 107 Succimer is less efficient in cases of zinc intoxication.…”
Section: (Molds) St (Yeasts)mentioning
confidence: 99%
“…Terbinafine has been administered to canines, lagomorphs, felines, and avian species via a variety of routes including those not evaluated in this study: intravenous, oral, and topical (Bechert, Christensen, Poppenga, Le et al., ; Bechert, Christensen, Poppenga, Fahmy, & Redig, ; Evans et al., ; Hosseini‐Yeganeh and McLachlan, ; Sakai et al., ; Sun et al., ; Wang et al., ; Williams et al., ). Oral administration is less practical for the treatment of snakes as these animals feed bimonthly and administration is more challenging in venomous species.…”
Section: Descriptive Pharmacokinetic Profile (Mean ± Sd) Of Cottonmoumentioning
confidence: 99%
“…All animals in this study tolerated terbinafine well and no clinical signs were observed; however, the long‐term effects of this drug in reptiles are unknown. Reported adverse effects in dogs are transient periocular swelling and erythema (Sakai et al., ) and regurgitation has been reported in avian species (Evans et al., ). Following intravenous administration, cats exhibited transient lassitude and a horse displayed transient head shaking and lip curling after receiving oral terbinafine (Wang et al., ; Williams et al., ).…”
Section: Descriptive Pharmacokinetic Profile (Mean ± Sd) Of Cottonmoumentioning
confidence: 99%
See 1 more Smart Citation